Identification of RNA-binding proteins in macrophages by interactome capture - Liepelt, Anke; Naarmann-de Vries, Isabel S.; Simons-Weidenmaier, Nadine; Eichelbaum, Katrin; Föhr, Sophia; Archer, Stuart K.; Castello, Alfredo; Usadel, Björn; Krijgsveld, Jeroen; Preiss, Thomas; Marx, Gernot; Hentze, Matthias W.; et al. (Molecular & cellular proteomics, 2016)
Pathogen components, such as lipopolysaccharides of gram-negative bacteria that activate Toll-like receptor 4, induce mitogen activated protein kinases and NFкB through different downstream pathways to stimulate pro- and anti-inflammatory cytokine expression. Importantly, post-transcriptional control of the expression of TLR4 downstream signaling molecules contributes to the tight regulation of inflammatory cytokine synthesis in macrophages. Emerging evidence highlights the role of RNA-binding proteins (RBPs) in the post-transcriptional control of the innate immune response. To systematically identify macrophage RBPs and their response to LPS stimulation, we employed RNA interactome capture in LPS-induced and untreated murine RAW 264.7 macrophages. This combines RBP-crosslinking to RNA, cell lysis, oligo(dT) capture of polyadenylated RNAs and mass spectrometry analysis of associated proteins. Our data revealed 402 proteins of the macrophage RNA interactome including 91 previously not annotated as RBPs. A comparison with published RNA interactomes classified 32 RBPs uniquely identified in RAW 264.7 macrophages. Of these, 19 proteins are linked to biochemical activities not directly related to RNA. From this group, we validated the HSP90 co-chaperone P23 that was demonstrated to exhibit cytosolic prostaglandin E2 synthase 3 (PTGES3) activity, and the hematopoietic cell-specific LYN substrate 1 (HCLS1 or HS1), a hematopoietic cell-specific adapter molecule, as novel macrophage RBPs. Our study expands the mammalian RBP repertoire, and identifies macrophage RBPs that respond to LPS. These RBPs are prime candidates for the post-transcriptional regulation and execution of LPS-induced signaling pathways and the innate immune response. Macrophage RBP data have been deposited to ProteomeXchange with identifier PXD002890.
Published as Manuscript M115.056564
Gesehen am 04.06.2020